Simple library cataloging - Akers, Susan Grey. (Chicago : American Library Association, 1954)
"Provides valuable guidance for librarians who work in small public, college, school, or special libraries and who have little formal training in the rudiments of cataloging."
Includes index
Includes bibliographical references.
aia 03/04/2018
Loans
Keywords: Cataloging